A Pilot Feasibility Study of PAL-CHW-PDAC, a Digitally Enhanced Community Health Worker-Led Intervention to Facilitate Stepped Palliative Care in Patients with Pancreatic Cancer - Nikhil R. Thiruvengadam; Maud Celestin-Joachim; Lizbeth Rivas; Nishita Matangi; Arman Bahmani; Matthew Oroso; Joel Brothers; Kendrick Che; Andrew Chang; Emmanuel Eguia; Paul Leonor; Gina Mohr; et al. (Journal of Palliative Medicine, 2026)
Background: Pancreatic Ductal Adenocarcinoma (PDAC) is associated with substantial morbidity and poor quality of life (QOL). Early palliative care (EPC) has been shown to improve QoL and reduce symptom burden in PDAC, but only a minority of PDAC patients receive it. Using three conceptual models, we developed a community health worker (CHW)-led intervention to help facilitate stepped PC. Objectives: To evaluate the feasibility, acceptability, and preliminary effectiveness of PAL-CHW-PDAC. Design: A single-center prospective single-arm pilot study. Setting/Subjects: Newly-diagnosed PDAC patients ( n = 48). Measurements: Acceptability and Feasibility were defined using the RE-AIM framework. Secondary outcomes were symptom burden, QOL, attitudes toward PC, and advance care planning (ACP) completion. Results: Ninety-four percent of patients strongly agreed that the intervention was acceptable. Themed common responses highlighted by patients centered around the critically important role of the CHW in their care, especially as symptoms worsened. Patients’ physical QoL and symptom burden improved from baseline to 12 weeks, while 83% of patients completed their ACP. Conclusions: The PAL-CHW-PDAC intervention was feasible and acceptable to PDAC patients and improved symptom burden. Prospective clinical trials are needed to assess the intervention’s ability to address the QOL needs of PDAC patients.